Comparison of characteristics between patients with H7N9 living in rural and urban areas of Zhejiang Province, China: a preliminary report. - Jimin Sun (PLoS ONE, 2014)
A total of 134 cases of H7N9 influenza infection were identified in 12 provinces of China between March 25 and September 31, 2013. Of these, 46 cases occurred in Zhejiang Province. We carried out a preliminary comparison of characteristics between rural and urban H7N9 cases from Zhejiang Province, China. Field investigations were conducted for each confirmed H7N9 case. A standardized questionnaire was used to collect information about demographics, exposure history, clinical signs and symptoms, timelines of medical visits and care after onset of illness. Of the 46 H7N9 cases in Zhejiang Province identified between March 25 and September 31, 2013, there were 16 rural cases and 30 urban cases. Compared to urban cases, there was a higher proportion of females among the rural cases [11/16 (69%) vs. 6/30 (20%), P = 0.001]. Among the rural cases, 14/15 (93%) with available data had a history of recent poultry exposure, which was significantly higher than that among urban cases (64%, P = 0.038). More patients from the rural group had a history of breeding poultry compared with those from the urban group [38% (6/16) vs. 10% (3/30), respectively; P = 0.025]. Interestingly, the median number of medical visits of patients from rural areas was higher than that of patients from urban areas (P = 0.046). There was no difference between the two groups in terms of age distribution, fatality rate, incubation period, symptoms, and underlying medical conditions. In conclusion, compared to patients from urban areas, more patients from rural areas were female, had an exposure history, had a history of breeding poultry, and had a higher number of medical visits. These findings indicate that there are different exposure patterns between patients living in rural and urban areas and that more rural cases were infected through backyard poultry breeding.